2019
DOI: 10.21203/rs.2.521/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acupuncture for poststroke hemiplegia focusing on bilateral cerebral connections: study protocol for a randomized controlled trial

Abstract: Background: Acupuncture is safe and effective for improving the motor function of poststroke hemiplegic patients, but there still exists a certain gap between clinical practice and its neural mechanisms. The cerebral functional reconstruction after unilateral motor pathway injury exhibits a bilateral tendency, however current studies seldom pay attention to it. Hence, based on bilateral cerebral connections, the underlying mechanism of acupuncture in stroke rehabilitation remains research space to date. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…Our previous work provided evidence for long-term acupuncture intervention effects using the voxel-mirrored homotopic connectivity method. We confirmed that Shou Zu Shi Er Zhen acupuncture prescription can integrate information among motor, vision, hearing processing, and cognitive brain regions, thereby promoting motor function recovery [23].…”
Section: Introductionsupporting
confidence: 64%
“…Our previous work provided evidence for long-term acupuncture intervention effects using the voxel-mirrored homotopic connectivity method. We confirmed that Shou Zu Shi Er Zhen acupuncture prescription can integrate information among motor, vision, hearing processing, and cognitive brain regions, thereby promoting motor function recovery [23].…”
Section: Introductionsupporting
confidence: 64%